EFEKTIVITAS PELATIHAN KARUNIA ROH ALLAH (PEKA) DALAM PEMBERDAYAAN SEMBILAN KARUNIA ROH ALLAH - Syekina Winniel Harun; Chandra Kirana Luhur; Wahyudi Sri Wijayanto (STT Kristus Alfa Omega, 2023)
Researchers suspect that the effectiveness of Pelatihan Karunia Roh Allah (PEKA) in empowering the nine gifts of God’s Spirit on GBI Sukawarna Gedebage church workers is less effective based on observations and interviews. This research aims to determine the level of effectiveness of PEKA in empowering the nine gifts of God’s Spirit on GBI Sukawarna Gedebage church workers using descriptive quantitative. Based on the hypothesis test obtained a level of effectiveness of PEKA in empowering the nine gifts of God's Spirit on GBI Sukawarna Gedebage Branch churchmen is in the very good category, which is 84%.